The light of Liberty: Symbol and history contained in an official newspaper of the state of Colima [1855-1862] - Valencia Ramírez, Jesús Adín (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2024)
This essay, ‘The light of freedom. Symbol and history contained in an official newspaper of the state of Colima [1855-1862]’, aims to contextualize from a semiotic understanding, various elements around an official nineteenth-century newspaper, published in a transcendental historical stage for Colima, during the Reform in our country.